Evaluation of the Impact of a senior mentor program on medical students' geriatric knowledge and attitudes toward older adults. Issue 3 (3rd July 2018) - Mendoza De La Garza, Maria; Tieu, Christina; Schroeder, Darrell; Lowe, Kathleen; Tung, Ericka
ABSTRACT: Medical schools throughout the country struggle with how best to train students to provide quality, patient-centered care to the burgeoning population of older adults. The Senior Sages Program (SSP) is a longitudinal Senior Mentor Program (SMP) that offers students the opportunity to learn about the aging process and core geriatric medicine concepts through the eyes of an aging expert: their Senior Sage. The SSP marries a robust electronic curriculum with an SMP and online discussion board. The aim of this program evaluation was to measure the impact on students' geriatric knowledge and attitudes toward older adults. This asynchronously facilitated course improved students' geriatric knowledge and facilitated stability of positive attitudes toward older adults. The majority of students felt that their SSP interactions were meaningful and valuable to their clinical development. The combination of SMP and electronic curricula offer a feasible, practical way to bridge the geriatric training chasm.